Measuring the ecological footprint of inbound and outbound tourists: Evidence from a panel of 35 countries - Qureshi, Muhammad Imran; Elashkar, Elsayed Elsherbini; Shoukry, Alaa Mohamd; Aamir, Alamzeb; Mahmood, Nik Hasnaa Nik; Md. Rasli, Amran; Zaman, Khalid (Springer-Verlag GmbH Germany, 2019)
The ecological footprint of tourism is imperative to assess for United Nation’s environmental sustainable agenda that is provoked for healthy visitation of tourists without damaging natural environment. This would ultimately reap economic and environmental benefts to sustained international tourism. This study examined the relationship between international tourism indicators, air pollutants, and ecological biodiversity underlying the premises of environmental Kuznets curve in the panel of 35 tourists-induced countries for the period of 1995–2016. The study used panel fxed efect and panel twostage least square regression technique for robust inferences. The results confrmed the following key points, i.e., (1) the U-shaped relationship found between inbound tourists and mono-nitrogen oxide (NOx), where inbound tourists initially do not emanate the NOx emissions, while at the later stages, the level of NOx emissions substantially raises the required strong policy intervention to reduce emissions and provide tourists safe and healthy destinations, (2) inbound tourists linked with the biodiversity loss, and it increases carbon dioxide (CO2) emissions and greenhouse gas (GHG) emissions in a panel of potential habitat area, while it decreases NOx and SO2 emissions, (4) international tourists’ departure exercised the ‘rebound efect’ on the ecosystem and air pollutants across countries, (5) there is a monotonic increasing relationship between outbound tourists and ecological footprint, while there is a fat/no relationship between outbound tourists, NOx, CO2, SO2, and GHG emissions, and (6) the food management practices supported the ecological diversity, and it reduces the carbon ‘foodprint,’ while it substantially increases SO2 emissions in outbound tourists’ model. The study emphasized the need for sustainable tourism infrastructure that conserves our natural environment and reduces climatic variability across the globe.